Perancangan UI/UX Fitur Customer Relationship Management (CRM) Pada Aplikasi ABC Reload Menggunakan Metode Design Thinking - Herman Kurniawan Gulo; Irsan Jaelani; Mochzen Gito Resmi (STMIK Budi Darma, 2023)
The ABC Reload app is a platform that connects customers with pulse recharge and bill payment services quickly and efficiently. In an era where customer interaction becomes successful, it is important for ABC Reload to strengthen relationships with customers through the implementation of Customer Relationship Management features (CRM). The design of the UI/UX user interface for the Customer Relationship Management (CRM) feature in the ABC Reload application has been done using the Design Thinking method. The study involved testing the feature with 30 respondents using the System Usability Scale method. (SUS). The design process of UI/UX features CRM on the ABC Reload application follows five main stages in the Design Thinking method, namely Empathize, Define, Ideate, Prototype and Test. Design Thinking methods are used to understand in depth the needs and preferences of users. Testing is done after UI/IX design is completed. The test results showed that the average value of the System Usability Scale (SUS) is 80,666, indicating that the design of UI/UX features CRM on the ABC Reload application received a positive response from users. It describes that the Design Thinking method applied in UI/UX design has succeeded in creating a more intuitive and user-satisfactory interface. Test results show that the Design Thinking method is able to meet the needs and wishes of the user well. The application of this method allows ABC Reload applications, especially for micro, small and medium-sized enterprises (MSMEs), to be more effective in managing customer relationships. Thus, the app can attract more customers and build a higher customer loyalty.